2014
DOI: 10.1089/jayao.2013.0028
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study to Measure Physical Activity, Fatigue, Sleep–Wake Disturbances, and Depression in Young Adults During Chemotherapy

Abstract: Little is known about the physical activity (PA) of young adults (YAs) during cancer therapy. In this feasibility study, 14 YAs (20-34 years old) completed a six-minute walk test, recorded their steps per day for one week, and answered weekly self-reports about physical activity, fatigue, sleep-wake disturbances, and depression during one cycle of chemotherapy. Findings suggest YAs are willing to complete a PA study during chemotherapy and have variable sleep and activity schedules. Their symptoms varied in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 24 publications
1
37
0
Order By: Relevance
“…Of the quantitative articles reviewed (n = 21; 66%), physical activity was treated as an outcome in 17 articles (81% 5,17,[38][39][40]43,44,[46][47][48][49][50][51][52][54][55][56] ), a moderator in 1 article (5% 45 ), a predictor in 1 article (5% 57 ), and a covariate in 2 articles (10% 41,42 ). # Ten of the quantitative articles (48%) explored the relationship between physical activity and descriptive (eg, age, cancer stage, and education), physical (eg, aerobic capacity, body mass index, and fatigue), personal/psychological (eg, mood, posttraumatic growth, and quality of life), social (eg, social support and support group involvement), other health behaviors (eg, smoking), and other factors (eg, program preferences/interest).…”
Section: Results From Quantitative Cross-sectional and Longitudinalmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the quantitative articles reviewed (n = 21; 66%), physical activity was treated as an outcome in 17 articles (81% 5,17,[38][39][40]43,44,[46][47][48][49][50][51][52][54][55][56] ), a moderator in 1 article (5% 45 ), a predictor in 1 article (5% 57 ), and a covariate in 2 articles (10% 41,42 ). # Ten of the quantitative articles (48%) explored the relationship between physical activity and descriptive (eg, age, cancer stage, and education), physical (eg, aerobic capacity, body mass index, and fatigue), personal/psychological (eg, mood, posttraumatic growth, and quality of life), social (eg, social support and support group involvement), other health behaviors (eg, smoking), and other factors (eg, program preferences/interest).…”
Section: Results From Quantitative Cross-sectional and Longitudinalmentioning
confidence: 99%
“…The remaining articles (n = 89) and the 43 articles for which we did not hear back from the corresponding authors were subsequently excluded . In total, 32 articles representing 26 unique studies met eligibility criteria and were therefore reviewed…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Adult PROMIS measures for fatigue, sleep disturbance, wake disturbance, and depression are acceptable and feasible for use with YAs receiving chemotherapy. 36 Because the pediatric item banks are specified for respondents ages 8 to 18 and the adult item banks for those over 18, PROMIS does not provide single instruments for use across the specific age range for AYAs.…”
Section: Resources For Measuring Symptoms and Symptom Clustersmentioning
confidence: 99%
“…Starting physiotherapy treatment during chemotherapy does not seem to produce side effects (Courneya et al, ), conversely, several authors found a positive impact in terms of physical activity (Braam et al, ; Erickson, Adelstein, & Letzkus, ; Velthuis, Agasi‐Idenburg, Aufdemkampe, & Wittink, ). Despite this indication, rehabilitation is rarely encouraged in the clinical practice during chemotherapy or it is postponed until the latter is finished.…”
Section: Introductionmentioning
confidence: 99%